Unravelling the Impact of Hypoxia, Reactive Oxygen Species, and Necrosis in Skeletal Muscles - Munir, Farwa; Manzoor, Farooq; Naeem, Shahzaib; Alsaedi, Emad Abdulrahman H.; Hamayoun, Maryum; Khan, Sher Wali; Baig, Atif Amin (International Health Review, 2025)
Skeletal muscle mass is strongly linked to stressors like ischemia and reactive oxygen species (ROS), both of which are regulated by oxygen availability and redox homeostasis. Intermittent ischemia and reperfusion cause a burst of reactive oxygen species, destruction of mitochondrial integrity, and inflammatory/necrotic pathways The objective of this review is to summarise existing data on the mechanistic interaction between hypoxia, ROS generation, and necrosis in skeletal muscle, as well as the role of these mechanisms in contributing to ischemia-reperfusion injury, metabolic disruption and dysfunction of skeletal muscle in the long term. The keywords examined in the literature search were skeletal muscle, hypoxia, reactive oxygen species, ischemia-reperfusion, mitochondria, and necrosis using PubMed, Scopus, and Web of Science. Articles published in English between 1990 and 2023 were peer reviewed and included, while conference abstracts, non-scientific reports, and duplicate records were excluded. The evidence suggests that hypoxia changes the use of substrates in the mitochondrion, stabilises the hypoxia-inducible factors and preconditions the muscle fibres to oxidative damage. The overproduction of ROS during reperfusion further increases the activity of inflammatory signalling, like NF-kB, calcium overload, and apoptotic and necrotic cell death. These teamed disruptions are what cause structural disintegration, dysfunctional contractional performance and retarded recuperation. An improved insight into these interrelated processes identifies prospects in therapeutic approaches such as antioxidants, enzymatic inhibition, gene-based treatment, cytokine therapy, and cell-derived exosomes- to alleviate ROS-related damage and promote muscle recovery.